Clericalization of the Russian Excursion Tourism - Rodoman, Boris (project baikal, 2014)
In the modern Russia almost every secular excursion is starting to resemble a religious pilgrimage, while reducing itself to a visit to Orthodox monasteries and temples. A lot of stories are told about saints and their actions, an unconcealed religious propaganda is carried on, and the history of the country is presented in a cleric-monarchical manner.